(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
In the climatic conditions of the Namangan region, during the years 2018-2021, scientific research was conducted on irrigation, fertilization and agrotechnics of 16 types of tulips introduced from the Netherlands.